Service Management in Crisis Individual Behavior and Circumstances of Misconditioning - Nurhalima, Nurhalima (Indonesian Journal Education, 2023)
The purpose of this study is to describe conditions that can occur in every individual suddenly known as a crisis condition that can experience an imbalance in life. Crisis is a pressure experienced by a person and negatively affects his ability to think, plan and deal with problems effectively. Guidance and Counseling for teachers/school counselors in dealing with crises cannot be separated from their duties, qualifications and competency standards. Guidance and Counseling Teachers/school counselors have duties, responsibilities, and authority in administering guidance and counseling services to students. The role of the Guidance and Counseling teacher/school counselor is indispensable in assisting with guidance and counseling, the school is a comfortable place for all parties, especially for students, especially in the implementation of crisis counseling. The description of a counselor's performance is not easy, but with his responsiveness and readiness, a counselor will be able to provide much better service with better results for the counselee he is serving and be ready to face various situations including crisis situations